The hospital results and 1-year outcomes of transcatheter aortic valve-in-valve procedures and transcatheter aortic valve implantations in the native valves: the results from the Swiss-TAVI Registry. (27th January 2019) - Ferrari, Enrico; Stortecky, Stefan; Heg, Dik; Muller, Olivier; Nietlispach, Fabian; Tueller, David; Toggweiler, Stefan; Noble, Stéphane; Maisano, Francesco; Roffi, Marco; Jeger, Raban; Grünenfelder, Jürg; et al.
Abstract: OBJECTIVES: The SwissTAVI Registry includes all consecutive patients undergoing transcatheter aortic valve implantation (TAVI) and valve-in-valve (VinV) procedures for a failed bioprosthesis in Switzerland. We report the real world, all-comers, 30-day and 1-year outcomes of patients undergoing VinV and standard TAVI procedures. METHODS: Prospectively collected data from the 2 groups (VinV and standard TAVI patients) were retrospectively analysed. In an adjusted analysis, in-hospital and 1-year outcomes of VinV patients were compared with those of patients undergoing TAVI for native aortic valve disease in the same registry. A subanalysis of VinV procedures in stenotic or regurgitant bioprosthesis was also performed. RESULTS: Between February 2011 and December 2016, 4599 and 157 consecutive patients underwent TAVI in native aortic valves and VinV procedures in degenerate bioprosthesis, respectively. VinV patients were younger (78 ± 9.1 years vs 82.2 ± 6.3 years; P < 0.001) but at a higher risk for surgery (the logistic EuroSCORE: 28.48 ± 15.3% vs 18.2 ± 13.6%; P < 0.001; the Society of Thoracic Surgery (STS) score: 6.4 ± 5% vs 5.5 ± 4.3%; P = 0.008). Valve predilatation was less frequently performed during VinV procedures (22.9% vs 69.1%; P < 0.001), and the hospital stay was shorter after VinV procedure (8.46 ± 4.2 days vs 9.83 ± 6 days; P = 0.005). VinV patients showed higher predischarge transvalvular mean gradients (14.14 ± 7.9 mmHg vs 8.42 ± 5.0 mmHg; P < 0.001), smaller mean valve surface area (1.54 ± 0.7 cm 2 vs 1.83 ± 0.5 cm 2 ; P < 0.001) and a lower risk of moderate/severe paravalvular leak (1.3% vs 5%). Post-procedural kidney injury (1.3% vs 4.8%; P = 0.06) and new pacemakers for conduction abnormalities (3.3% vs 18.5%; P < 0.001) were higher after TAVI. All-cause mortality and cardiovascular mortality at 30 days were similar between the 2 groups (1.9% vs 3.8%; P = 0.242 and 1.9% vs 3.4%; P = 0.321), whereas after 1 year, all-cause mortality was lower for VinV patients (6.8% vs 13%; P = 0.035). The bioprosthetic valve size correlated inversely with postoperative gradients after VinV procedures. CONCLUSIONS: VinV aortic procedures showed favourable 30-day and 1-year clinical outcomes compared with TAVI procedures for the native aortic valve disease. Despite higher transvalvular mean gradients following VinV implants, this appears not to impact the early clinical outcomes.